Soya bean machine - anon (Ministry of Education, Thailand, 2013)
This invention has been participated at the 8th International Exhibition for Young Inventors (IEYI 2012), 28th - 30th June 2012 held at Bangkok International Trade and Exhibition Centre (BITEC), Bangkok, Thailand.